Novel approaches in cognitive informatics and natural intelligence - Wang, Yingxu (Hershey, PA : Information Science Reference, 2009)
'This book covers issue of cognitive informatics with a transdisciplinary enquiry of cognitive and information sciences that investigates the internal information processing mechanisms and processes of the brain and natural intelligence, and their engineering applications via an interdisciplinary approach'--Provided by publisher.
'Premier reference source'--Cover.
Includes bibliographical references (p. 335-362) and index.
Keywords: Neural computers; Cognitive science; Artificial intelligence